A randomized crossover trial of elamipretide in adults with primary mitochondrial myopathy. Issue 4 (25th February 2020) - Karaa, Amel; Haas, Richard; Goldstein, Amy; Vockley, Jerry; Cohen, Bruce H.
Abstract: Background: This study aims to evaluate the effect of subcutaneous (SC) elamipretide dosing on exercise performance using the 6 min walk test (6MWT), patient‐reported outcomes measuring fatigue, functional assessments, and safety to guide the development of the Phase 3 trial. Methods: MMPOWER‐2 was a randomized, double‐blind, placebo‐controlled, crossover trial that enrolled participants ( N  = 30) with genetically confirmed primary mitochondrial myopathy. Participants were randomly assigned (1:1) to 40 mg/day SC elamipretide for 4 weeks followed by placebo SC for 4 weeks, separated by a 4‐week washout period, or the opposite sequence. The primary endpoint was the distance walked on the 6MWT. Results: The distance walked on the 6MWT by the elamipretide‐treated participants was 398.3 (±134.16) meters compared with 378.5 (±125.10) meters in the placebo‐treated group, a difference of 19.8 m (95% confidence interval, −2.8, 42.5; P  = 0.0833). The results of the Primary Mitochondrial Myopathy Symptom Assessment Total Fatigue and Total Fatigue During Activities scores showed that participants treated with elamipretide reported less fatigue and muscle complaints compared with placebo ( P  = 0.0006 and P  = 0.0018, respectively). Additionally, the Neuro‐QoL Fatigue Short Form and Patient Global Assessment showed reductions in symptoms ( P  = 0.0115 and P  = 0.0421, respectively). In this 4‐week treatment period, no statistically significant change was observed in the Physician Global Assessment ( P  = 0.0636), the Triple Timed Up and Go ( P  = 0.8423) test, and wrist/hip accelerometry ( P  = 0.9345 and P  = 0.7326, respectively). Injection site reactions were the most commonly reported adverse events with elamipretide (80%), the majority of which were mild. No serious adverse events or deaths were reported. Conclusions: Participants who received a short‐course treatment of daily SC elamipretide for 4 weeks experienced a clinically meaningful change in the 6MWT, which did not achieve statistical significance as the primary endpoint of the study. Secondary endpoints were suggestive of an elamipretide treatment effect compared with placebo. Nominal statistically significant and clinically meaningful improvements were seen in patient‐reported outcomes. The results of this trial provided an efficacy signal and data to support the initiation of MMPOWER‐3, a 6‐month long, Phase 3 treatment trial in patients with primary mitochondrial myopathy.